The Effect of Academic Motivation on RPL Program Students’ English Proficiency Test Score - Atik Ulinuha; Setyani Alfinuha (SALEE: Study of Applied Linguistics and English Education, 2023)
The need for education is increasing and getting more complex along the time for it is a crucial need to prepare better human resources. Currently, higher education is attended by adult learners who are not only study but also work in the industry since the competition in the workplace is getting harder in this globalization era which implicitly requires English proficiency of the workers. Those who work while study must have a motivation either intrinsic or extrinsic to pursue higher education. Thus, this study aims to investigate the effect of academic motivation on RPL program students’ English proficiency test score. This study employed a descriptive quantitative method involving 27 RPL program students majoring in Pharmacy. Data obtained from the Academic Motivation Scale and students’ TOEIC scores were analyzed quantitatively using simple linear regression technique with the help of SPSS 22.0. This study found that even though the data were normal and linear, academic motivation had no effect on the students’ English proficiency test scores. This might happen because there are way more complex factors that influence academic achievement or academic performance in the results of English proficiency test.